2018
DOI: 10.1002/cam4.1709
|View full text |Cite
|
Sign up to set email alerts
|

Proactive community support tailored to holistic needs: A cohort study

Abstract: BackgroundIt is increasingly internationally recognized that a cancer diagnosis impacts on people practically and financially as well as physically and psychologically. It is less clear what to do about this. This study introduces an original community service designed to mitigate this wider impact. Nonclinical “link officers” use holistic needs assessment (HNA) to help newly diagnosed people identify and quantify the severity of their physical, psychological, practical, financial, and social concerns. A care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 27 publications
4
17
0
Order By: Relevance
“…line with previous findings [9]. Figure 3 shows the mean change in the different domains of the HNA.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…line with previous findings [9]. Figure 3 shows the mean change in the different domains of the HNA.…”
Section: Resultssupporting
confidence: 90%
“…This study has described a significant association between change in HNA score and self-reported health status. Following intervention from ICJ, mean HNA concern severity reduced from 6.4 [6.23-6.71] to 2.9 [2.66-3.13], consistent with the decrease seen in the wider ICJ population [9]. Concurrently, EQ-5D score increased from 0.45 [0.422-0.488] to 0.57 [0.547-0.604], while VAS scores increased from 49 [47.1-51.1] to 57 [54.9-58.9].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The time between assessments ranged from 14 to 456 days, averaging 117 days (median 84). Between baseline and follow up, self reported severity of concern dropped, in line with previous ndings [9]. Figure 3 shows the mean change in the different domains of the HNA.…”
Section: Resultssupporting
confidence: 83%